Human phosphatase CDC14A is recruited to the cell leading edge to regulate cell migration and adhesion - Chen, Nan-Peng; Uddin, Borhan; Voit, Renate; Schiebel, Elmar (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Cell adhesion and migration are highly dynamic biological processes that play important roles in organ development and cancer metastasis. Their tight regulation by small GTPases and protein phosphorylation make interrogation of these key processes of great importance. We now show that the conserved dual-specificity phosphatase human cell-division cycle 14A (hCDC14A) associates with the actin cytoskeleton of human cells. To understand hCDC14A function at this location, we manipulated native loci to ablate hCDC14A phosphatase activity (hCDC14APD) in untransformed hTERT-RPE1 and colorectal cancer (HCT116) cell lines and expressed the phosphatase in HeLa FRT T-Rex cells. Ectopic expression of hCDC14A induced stress fiber formation, whereas stress fibers were diminished in hCDC14APD cells. hCDC14APD cells displayed faster cell migration and less adhesion than wild-type controls. hCDC14A colocalized with the hCDC14A substrate kidney- and brain-expressed protein (KIBRA) at the cell leading edge and overexpression of KIBRA was able to reverse the phenotypes of hCDC14APD cells. Finally, we show that ablation of hCDC14A activity increased the aggressive nature of cells in an in vitro tumor formation assay. Consistently, hCDC14A is down-regulated in many tumor tissues and reduced hCDC14A expression is correlated with poorer survival of patients with cancer, to suggest that hCDC14A may directly contribute to the metastatic potential of tumors. Thus, we have uncovered an unanticipated role for hCDC14A in cell migration and adhesion that is clearly distinct from the mitotic and cytokinesis functions of Cdc14/Flp1 in budding and fission yeast.
Gesehen am 30.04.2020